2020
DOI: 10.1001/jamanetworkopen.2020.29682
|View full text |Cite
|
Sign up to set email alerts
|

USPSTF Recommendations for Behavioral Counseling in Adults With Cardiovascular Disease Risk Factors

Abstract: The United States Preventive Services Task Force (USPSTF) has released new recommendations for adults with known cardiovascular disease (CVD) risk factors 1 and an associated systematic literature review. 2 The recommendations encourage medical practitioners to offer or refer adults with CVD risk factors to behavioral counseling interventions to promote healthy diet and physical activity (B recommendation). 1,2 Notable changes from the 2014 recommendations are that recommendations are extended to patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…20 Additionally, telemedicine can provide access to healthcare without disrupting one's workday or reducing daily wages. 19 These advantages have been summarized in Figure 3.…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…20 Additionally, telemedicine can provide access to healthcare without disrupting one's workday or reducing daily wages. 19 These advantages have been summarized in Figure 3.…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%
“…By providing healthcare to neglected communities' telemedicine can help reduce racial, ethnic, and socioeconomic inequalities. However, this is only possible if measures are taken to address concerns involving the accessibility of broadband and wifi by members of such communities 19 Telemedicine also offers a solution for people who cannot access healthcare due to their reduced mobility and offers a cost‐effective approach to healthcare. Individuals can save time that would otherwise be spent traveling and waiting for appointments.…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%
“…25 This underscores the critical need for clinicians to collaborate with other members of the health care team, community, or other organizations/services to facilitate patient access to an effective level of behavioral counseling. A number of other barriers to the 2020 USPSTF Recommendations and delivery of lifestyle-related behavior change in clinical practice have been previously described related to the health care system and reimbursement, 22,37,38 which are outside the scope of this advisory. Here, we describe each of the 5As and intervention strategies for clinician-led implementation in clinical practice.…”
Section: Behavior Change Strategies For Addressing Lifestyle Behavior...mentioning
confidence: 99%
“…Virani et al (2020) state that more than a quarter of CVD deaths can be prevented yearly with proper preventive medical care. Many studies have shown that behavioral counseling facilitated by healthcare professionals can improve CVD risk behaviors and reduce outcomes for known CVD risk factors in adults ( Kharmats et al, 2020 ). According to the 2019 American College of Cardiology/American Heart Association (ACC/AHA) Guideline on the Primary Prevention of Cardiovascular Disease, behavioral counseling should be used as the first line of treatment for promoting cardiovascular health behaviors and reducing risk factors ( Arnett et al, 2019 ; Laddu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%